EVALUATION OF BIOCHEMICAL AND MICROBIOLOGICAL CHANGES OCCURRING IN FRESH CHEESE WITH ESSENTIAL OILS DURING STORAGE TIME - FOGARASI, Melinda; SOCACI, Sonia Ancuța; FOGARASI, Szabolcs; JIMBOREAN, Mirela; POP, Carmen; TOFANĂ, Maria; ROTAR, Anca; ȚIBULCĂ, Dorin; SĂLĂGEAN, Dan; SALANȚĂ, Liana-Claudia (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The current study aimed to determine the chemical composition and antibacterial activity of two essential oils extracted from herbs belonging to the family Lamiaceae (mint and oregano), and their beneficial impact on the biochemical and microbiological changes occurring in fresh cheese during storage time. Based on the essential oils results three types of fresh cheese were formulated and the samples consumers preferred were sensory rated using the 9-point hedonic test. In order to determine the stability during storage, the selected sample and the essential oil free control sample were sampled initially, after 6 and 12 days of storage than subjected to physicochemical (protein, fat, moisture, ash, total carbohydrates, and energy) and microbiological analyses (S. aureus, E. coli).